The challenges in the intellectualisation of indigenous languages in post-apartheid South Africa: what will it take to give the indigenous languages a directive in the implementation and monitoring of language policy in South Africa? - Ntentema, Phakamani (African Languages and Literatures, 2021)
The language of an individual is another skin in ways that are many, a natural possession of any normal person we use to communicate our ideas and hopes, convey our beliefs and thoughts, explore our traditions and experiences, and improve the community of ours as well as the laws that regulate it. In the Bill of Rights, the right of official language selection was recognized, and the Constitution recognizes that the indigenous languages are a resource that has not been exploited. This study has been carried out to elevate the use and uplift the status of indigenous languages by examining the challenges of intellectualizing the indigenous languages in post-apartheid South Africa. The language choice in South Africa does not favour the indigenous languages. The South African government lacks the political will to practically implement the language policies. The gab is in the lack of monitoring the process of language policy and implementation. Some South African higher education institutions have clear plans to implement the language policies, and some do not. The English language dominance in the higher education system has negatively impacted the indigenous students and denigrated the indigenous language use and intellectualization. There is also a gap between the indigenous speakers and the language policy implementers. This study focused on youth from the indigenous speaking background. This study was carried out to get the voices of the indigenous youth regarding lack of implementation of language policies that are placed to develop and uplift the status and use of indigenous languages all domains and how that disadvantaged them from their point of view. This study has applied the qualitative methodology to collect the data. This study also applied the Critical Discourse Analysis and Critical Language Awareness theories to analyse the findings. These theories have awakened the indigenous speakers about the power dynamics that influences the lack of implementation of language policies. This study utilized the Interpretation-focus coding strategy to analyse the data. This study explored whether languages could provide access to change, social and material conditions of its speakers and the study found that the lack of implementation of indigenous languages correlates to the delay in development of the material conditions of the indigenous speakers and languages provide access to economic, social, material, and economic changes. Multilingualism is a way forward in resolving the language issue as South Arica is a multi-lingual nation. The limitations of the study were that it was carried out during the COVID-19 era and the hard South African lockdown.